Harnessing oleaginous yeast to produce omega fatty acids - Lin,L; Ledesma-Amaro,R; Ji,X-J; Huang,H (Trends in Biotechnology, 2024)
Omega fatty acids are important for human health. They are traditionally extracted from animals or plants but can be alternatively produced using oleaginous yeast. Current efforts are producing yeast strains with similar fatty acid distributions and powerful lipogenesis capacity. The next step is to further make the process more competitive.